Neurological worsening during treatment of an immunocompetent adult with Cryptococcus neoformans meningitis - Tanu, Singhal (Med Mycol Case Rep, 2020)
Cryptococcal meningitis is being increasingly described in immunocompetent adults. We describe here a young immuncompetent adult of Indian origin from Ghana, West Africa with cryptococcal meningitis who had several ups and downs during his treatment. First he developed neurologic worsening due to premature transition from intensive to consolidation phase therapy. Subsequently he deteriorated due to “immune reconstitution inflammatory syndrome (IRIS)” like phenomenon that necessitated the prolonged use of steroids. Additionally he suffered serious adverse effects due to antifungal drugs including liposomal amphotericin B and flucytosine. He recovered after 16 months of treatment. The case highlights the possible difficulties in management of cryptococcal meningitis in immunocompetent host including ‘immune reconstitution like syndrome’. There is need for new trial data and guidelines about treatment of cryptococcosis in the non HIV host.